2022
DOI: 10.1155/2022/7058477
|View full text |Cite|
|
Sign up to set email alerts
|

Research on Material Design of Medical Products for Elderly Families Based on Artificial Intelligence

Abstract: Due to the rapid growth of the elderly around the world, the artificial intelligence control framework can collect information and apply it and perform other tasks. Artificial intelligence plays an important role in focusing on the elderly. For example, it can improve the relationship between the elderly and family members or nursing teams. In addition, AI chat robot can communicate with the elderly without obstacles and can remind the elderly when to take medicine, regular physical examination, etc. A signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…The topic of artificial intelligence is currently being covered in a significant number of articles across the domestic web. There are a number of well-known papers on the subject of artificial intelligence, such as "Application of Artificial Intelligence in Health Care," "Consensus, Differences, and Problems in Artificial Intelligence Education: Content Analysis Based on Four Sets of Standard Documents," and "Research on the use of intelligent caregiving robots in the homefrom the perspective of empty nesters' environments" [6][7][8]. Due to the fact that these discussions and research are primarily conceptual descriptions of how artificial intelligence is applied to caregiving robots or other fields [9,10], there is no systematic discussion or research on artificial intelligence in the environment pertaining to public healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…The topic of artificial intelligence is currently being covered in a significant number of articles across the domestic web. There are a number of well-known papers on the subject of artificial intelligence, such as "Application of Artificial Intelligence in Health Care," "Consensus, Differences, and Problems in Artificial Intelligence Education: Content Analysis Based on Four Sets of Standard Documents," and "Research on the use of intelligent caregiving robots in the homefrom the perspective of empty nesters' environments" [6][7][8]. Due to the fact that these discussions and research are primarily conceptual descriptions of how artificial intelligence is applied to caregiving robots or other fields [9,10], there is no systematic discussion or research on artificial intelligence in the environment pertaining to public healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%